Herbal medicine : biomolecular and clinical aspects - Benzie, Iris F. F.; Wachtel-Galor, Sissi (Oxidative stress and disease, 2011)
"Responding to the increased popularity of herbal medicines and other forms of complementary or alternative medicine in countries around the world, this reference reviews and evaluates various safety, toxicity, and quality-control issues related to the use of traditional and herbal products for health maintenance and disease prevention and treatment. With over 3,550 current references, the book highlights the role of herbal medicine in national health care while providing case studies of widely used herbal remedies and their effects on human health and wellness and the need for the design and performance of methodologically sound clinical trials for the plethora of herbal medicines" -- Provided by publisher